Effect of prepartum protein level on calf birth weight, calving difficulty, and reproductive parameters of first calf heifers and mature beef cows - R.P. Bolze; L.R. Corah; G.M. Fink; L. Hoover (Kansas Agricultural Experiment Station Research Reports, 1985)
Two trials were conducted to determine if precalving protein intake would influence calf birth weight and calving difficulty. In Trial 1 (1983), 38 spring-calving Simmental heifers and 49 cows were allotted to three, 112 day isocaloric prepartum nutritional treatments: 75 (low), 100 (control) or 150 (high) percent of daily crude protein requirements (1976 NRC) for heifers or cows in the last trimester of pregnancy. In Trial 2 (1984), 22 heifers and 51 cows were allotted to control and high protein treatments only. After calving, cows were fed to meet NRC requirements. In Trial 1, the low protein level decreased prepartum weight gain but had no effect on postpartum weight change, pre-or postpartum condition change, postpartum interval (PPI), percent cycling is the first 21 days of the breeding season, first service or overall conception, milk production, calving difficulty, calf birth or 205 day weight. In both trials, high protein intake increased prepartum weight gain and condition score, shortened the PPI and increased percent cycling in first 21 days of breeding season but had no effect on the first service or overall conception, milk production, calving difficulty calf birth or 205 day weight.
Keywords: Cattlemen' s Day; 1985; Kansas Agricultural Experiment Station contribution; no. 85-319-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 470; Beef; Protein; Birth weight; Reproduction